(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The higher level of human activities has resulted in several forms of anthropogenic activities with diverse adverse effects on human and environmental sustainability. The traditional means of handling xenobiotics pollutants are no longer sustainable due to the high cost involved, complex procedures and demanding regulatory requirements. Bioremediation using fungi (mycoremediation) is now recognized as an efficient and workable biotechnological tool that effectively employ fungal enzymes via the process of absorption and mineralization to get rid of contaminants. Cytochrome P450s (CYPs) are diverse and unique gene families with varying degree of complexities in the eukaryotes. CYPs mainly utilize molecular oxygen to modify substrate conformation, thereby establishing a mechanism of action for achieving their important physiological and ecological processes. Xylariaceae belongs to the main and highly diversified families of filamentous Ascomycota; it plays an important role as saprotrophs of wood, soil, litter and dung. Genome-wide annotation analysis was carried out to explore the possibility of utilizing the CYPs of Xylaria sp. for achieving mycoremediation. The evolutionary analysis has divided the 214 Xylaria CYPs into fifteen (15) clades. The CYPs were categorized into forty-seven (47 clans) and eighty-six (86) families. MEME suite identified ten (10) conserved motifs. The gene structural investigation reveals high dynamic intron-exon organization. Most of the CYPs have been predicted to be localized in the endoplasmic reticulum. This study therefore calls for deeper exploration of the Xylaria sp and its high potential for application in bioremediation for the degradation of environmental contaminants.